Modeling of the System "Concentrated Stream of Energy - Metal" Dynamics. Equation of State; The 7th International Forum on Strategic Technology (IFOST-2012), September 18-21, 2012, Tomsk - Daneykin (Daneikin) Yu. V. Yuri Viktorovich (2012, 2012)
Title screen